Evaluation of the Anti-Corruption Education Policy within the Civil Servant Apparatus (ASN) in the Central Java Province - Hendri Santosa (Jurnal Penelitian Pendidikan, 2023)
This study aims to assess the alignment and precision of policy formulation, the quality of policy implementation, the policy's suitability, and the effectiveness of the anti-corruption education program for civil servants (ASN) established through Governor Regulation No. 10/2019 in Central Java. This research employed a qualitative research design with a descriptive approach. The subjects of the study consisted of 23 participants, including five structural and functional officials from the Central Java Regional Training and Education Center (BPSDMD), six trainers from BPSDMD, two anti-corruption instructors from the Inspectorate of Central Java Province, and ten training participants at BPSDMD in Central Java. The data for this study comprised primary data obtained from interviews and secondary data including journals, books, and articles. The evaluation uses the Context, Input, Process, Product (CIPP) evaluation model. Data collection techniques involved in-depth interviews and documentation, collecting data such as interview transcripts and documents related to anti-corruption education from BPSDMD in Central Java. The research findings indicate that there is alignment and precision in the formulation of the anti-corruption education policy for civil servants as stipulated in Governor Regulation No. 10/2019, and the policy has achieved its intended goals. The anti-corruption education policy has demonstrated quality, and there is congruence between the policy and its implementation environment. The anti-corruption program for civil servants in Central Java has been effective. Recommendations for improvement include the need for annual program updates to maximize evaluation improvements, more extensive anti-corruption education, the establishment of Integrity Seeds within each local government organization, and the necessity for more intensive collaboration between BPSDMD, the Inspectorate, the Central Java Anti-Corruption Educator Community, and the Corruption Eradication Commission (KPK).